Studies on Genomic Sequences For the Heat Shock Proteins hsp60 and hsp10 From Chinese Hamster Ovary Cells - Zurawinski, Joni (My University, 1997)
Although the eDNA sequences for the 10 k:Da (hsp 10, hsp 1 0) and the 60 k:Da (hsp60, cpn60) heat shock proteins have been obtained for a number of mammalian species, until very recently information was not available on the functional genes encoding these proteins. The primary objective of this work was to clone and sequence the functional genes for these proteins from CHO, Chinese hamster ovary cells. Screening of a lambda EMBL3 CHO genomic library with the CHO hsp 10 eDNA identified a clone containing the putative hsp 10 functional gene. A -5.5 kb fragment was isolated from one of these clones by enzymatic digestion and -3.3 kb was sequenced. The clone was found to contain consensus regulatory sequences upstream of the putative transcription initiation site, + 1, including two Sp 1 binding sites, a CAAT box, and a single heat shock element, HSE, but lacked a TATA box. The coding region consists of four exons, identical to the hsp10 CHO eDNA sequence, separated by three introns, of 200 bp, 600 bp and 1600 bp in size, containing conserved splice sites. Screening of the same EMBL3 CHO genomic library with the CHO hsp 10 eDNA also resulted in isolation of a full length processed pseudogene with -90 % identity to the eDNA. This pseudogene lacked introns, contained a poly(A) tract, as well as various single bp changes, additions and deletions. The upstream region of this pseudo gene was found to contain similarity to the human LINE sequence, a DNA repetitive element. PCR amplification ofCHO-WT genomic DNA resulted in isolation offive additional processed pseudogenes, corresponding to the central -270 bp of the CHO hsplO eDNA. All the pseudogenes displayed a high degree of similarity to the CHO hsp 10 eDNA sequence despite the presence of numerous mutations. Prior to this report, pseudogenes had not been found associated with hsp 10. The identification of these pseudogenes suggests the presence of a multi gene family for this heat shock protein in the CHO genome. Previously, a semi-processed pseudogene, Gel, was identified for hsp60 from CHO cells which contained a single -87 bp intron near its 3' end (Venner eta/., 1990). From this pseudo gene, a fragment containing the -87 bp intron was isolated for use as a probe to screen a lambda EMBL3 CHO genomic library. This resulted in isolation of several positive clones, two of which were purified, a -1.0 kb fragment amplified by PCR and then sequenced revealing two additional semi-processed pseudogenes, designated .A4 and .AS. These pseudo genes were found to be homologous to the GC 1 clone, containing many similar mutations as well as the -87 bp intron. Utilizing CHO-WT genomic DNA, a separate PCR amplification resulted in isolation of a -2.5 kb fragment which was partially sequenced and found to correspond to the putative hsp60 functional gene. The fragment contained one exon, which was identical to the CHO hsp60 eDNA in the region sequenced, and two introns of800 bp and 1500 bp. This fragment can now provide an ideal probe for isolation ofthe CHO hsp60 functional gene.
Keywords: cDNA sequences, heat shock proteins, Chinese hamster ovary cells, genomic library, regulatory sequences